Disodium cromoglycate in the treatment of ulcerative colitis and Crohn's disease. Issue 1 (January 1981) - Binder, V; Elsborg, L; Greibe, J; Hendriksen, C; Høj, L; Jensen, K B; Kristensen, E; Madsen, J R; Marner, B; Riis, P; Willumsen, L
Abstract : A controlled clinical study on disodium cromoglycate (DSCG) at a dose of 800 mg per day versus placebo was carried out in 141 patients with ulcerative colitis and 25 patients with Crohn's disease. Those of the ulcerative colitis patients who had been on sulphasalazine treatment continued that treatment during the trial (101 patients). Forty patients were intolerant of sulphasalazine. No patient received steroids during the last month before the study. Patients with Crohn's disease had their possible sulphasalazine treatment stopped before the trial. No beneficial effect of DSCG as compared with placebo was found, as the DSCG and the placebo group showed the same number of relapses in patients with a clinically inactive ulcerative colitis at the start of the trial and the same number of patients improving, deteriorating, and maintaining steady state in patients with clinically active ulcerative colitis at the start of the trial. There was no difference between relapse rate in DSCG and placebo groups in patients with Crohn's disease. No correlation between the eosinophil count in rectal mucosa and the outcome of the attack of ulcerative colitis could be demonstrated.